2021
DOI: 10.1371/journal.ppat.1009194
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial dormancy: A subpopulation of viable but non-culturable cells demonstrates better fitness for revival

Abstract: The viable but non culturable (VBNC) state is a condition in which bacterial cells are viable and metabolically active, but resistant to cultivation using a routine growth medium. We investigated the ability of V. parahaemolyticus to form VBNC cells, and to subsequently become resuscitated. The ability to control VBNC cell formation in the laboratory allowed us to selectively isolate VBNC cells using fluorescence activated cell sorting, and to differentiate subpopulations based on their metabolic activity, cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…VBNC was first reported by Xu et al [ 30 ], and this finding was subsequently confirmed by several independent studies, with VBNC now commonly recognized as a critical survival strategy for bacteria [ 31 ]. Furthermore, a number of studies have been carried out globally on VBNC [ 32 , 33 , 34 ], showing the importance of this state on the bacterial life cycle and the implications for the relationship of bacteria with other species, including their hosts. However, there are no reports of VBNC in C. diphtheriae , despite the fact that C. diphtheriae is recognized as a reemerging human pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…VBNC was first reported by Xu et al [ 30 ], and this finding was subsequently confirmed by several independent studies, with VBNC now commonly recognized as a critical survival strategy for bacteria [ 31 ]. Furthermore, a number of studies have been carried out globally on VBNC [ 32 , 33 , 34 ], showing the importance of this state on the bacterial life cycle and the implications for the relationship of bacteria with other species, including their hosts. However, there are no reports of VBNC in C. diphtheriae , despite the fact that C. diphtheriae is recognized as a reemerging human pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…The use of IFC allowed the authors to first identify sub-populations by imaging and SSC profiles. The authors then combined this with traditional fluorescently activated cell sorting to collect different cell morphological populations and show further differences in proteome profiles ( Wagley et al., 2021 ). This further highlights the importance of flow cytometry data to be visually confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental stresses, including the availability of nutrients ( Westfall and Levin, 2018 ), oxygen ( Murashko and Lin-Chao, 2017 ), and pH changes ( Ingham et al., 2008 ) may also result in bacteria adapting their shape in response to these environmental changes. Examples of such adaptation include the production of spores in Bacillus subtilis in response to starvation ( McKenney et al., 2013 ), the generation of filamentous cells in Lactoplantibacillus plantarum in response to acidification ( Ingham et al., 2008 ) and exposure to antibiotics ( Maki et al., 2000 ) or the transition to a dormant “viable but non-culturable” (VBNC) state in response to potentially lethal changes in the environment ( Dewachter et al., 2019 ; Wagley et al., 2021 ). These dormant states in bacteria are often accompanied by a shift in morphology as their metabolic state changes.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that the exposure to visible light along with variations in temperature, salinity, and others, might promote the V. harveyi entry to the VBNC state in aquatic systems. Moreover, several studies have proposed that the VBNC cells can potentially preserve their capacity to elicit infections [6,39,80]. Further analysis of cell envelope subproteome revealed that a number of membrane proteins playing the key roles in maintenance of major cell envelope functions constitute a pool of proteins continuously present in viable (culturable and nonculturable) V. harveyi ATCC14126 T populations exposed to stress.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the starved V. harveyi cells varied along the survival process, in fact, the cells reduced considerably their length during incubation, from a medium length of 1.93 µ m at the beginning of the experiments to 0.97 or 0.92 µ m after 21 d of incubation in the absence or presence of illumination, respectively. These phenotypical changes led to the appearance of cells with the coccoid-like morphology associated with the VBNC state in Vibrio species [39]. The length reduction was more profound when the experiments were carried out under illumination.…”
Section: Analysis Of V Harveyi Persistence At 20 • Cmentioning
confidence: 99%